A CORPUS-BASED STUDY OF REPORTING VERBS IN DAN BROWN'S THE LOST SYMBOL: A TRANSLATIONAL PERSPECTIVE - Talitha Disti Amalia, - (2012)
The study focuses on depicting the frequency of reporting verbs appearing in the source language (SL), analysing the procedures of translating reporting verbs from English as source languange (SL) to Indonesian as target language (TL) and assessing the accuracy of the translation. The study employs descriptive research which uses corpus-processing software to compile the data and manually analyse the data. The data is taken from one of the world's best-selling novel entitled The Lost Symbol written by Dan Brown and its translation version. The result of corpus-based analysis shows that from 41 reporting verbs appearing in SL said (36%) is the most frequent reporting verb in the novel, followed by replied (7%), whispered (6%), shouted (6%) and asked (5%). It also shows that agreed, gasped, groaned, looked, muttered, and screamed as the less frequent reporting verbs with only one occurrence each verb. Furthermore, the analysis shows that procedures occuring in the study are Literal translation (73%), Synonymy (14%), Equivalence (9%) and Expansion (4%). Based on the questionnaire given to three professional translators, it can be concluded that the translation is accurate. There is no significant mistake in translating the reporting verbs. It still conveys the meaning from the SL to TL so it still can easily be understood by the readers.